Evaluasi User Experience Pada Gim Clash of Clans Menggunakan Metode UX Curve - Ari Bayu Prasetyo; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Clash of Clans is a game with a strategy genre created by a world famous game company from Finland and was founded in August 2012. This game was initiated by the game's CEO, Ikka Paananen. At first this game was only released for smartphones, namely iOS only, the following year the Android version was released. There are 5 parts of the UX Curve method that are used as question parameters to game users, namely, General UX, Attractiveness, Ease-of-use, Utility and finally Degree-of-usage. After the process, the categories can be broken down into three categories, namely Improving, Deteriorating, and Stable. The result is 65 Improving category curves, 9 Deteriorating category curves and the last 26 Stable category curves. There are other aspects besides the depiction of curves, respondents are instructed to make reasons for their experience using the application and categorize them into positive reasons and negative reasons. In the General UX aspect, the mean reason is 3.5, the mean attractiveness of the reason is 2.9, the average Ease-of-use reason is 2.9, the average utility reason is 2.7, the Degree-of-use average reason is 3.1. It can be concluded that users of the Clash of Clans game mostly use games in their daily lives as entertainment and gather online and play together. As well as respondents if friends plan to use this game in the future they are enthusiastic about making recommendations for the use of this Clash of Clans game.